Estimation of Serum Uric Acid and Correlation with Clinical Findings in Stroke Patients Using National Institute of Health Stroke Scale - K.R. Sharan; Prabhu Gnanasekaran; Suresh K (The Bioscan, 2025)
Stroke remains a leading cause of global morbidity and mortality, with ischemic strokes accounting for nearly 87% of all cases. Emerging evidence highlights serum uric acid (SUA) as a potential biomarker for stroke prognosis, although its role remains paradoxical—demonstrating both neuroprotective and neurotoxic effects. This cross-sectional study conducted in a tertiary care centre at Puducherry aimed to investigate the correlation between SUA levels and stroke severity, as measured by the NIH Stroke Scale (NIHSS), in 118 patients aged above 40 years. Demographic and clinical variables—including age, gender, hypertension, diabetes, smoking habits, and drug history—were systematically recorded. SUA levels were stratified and analyzed against NIHSS scores to evaluate stroke severity and short-term outcomes. Results indicated a statistically significant association: patients with elevated SUA levels exhibited markedly higher NIHSS scores, reflecting greater stroke severity. Notably, SUA levels increased significantly with age, and a majority of patients with very severe stroke had SUA levels exceeding 6.0 mg/dL. These findings support the hypothesis that elevated SUA is correlated with poorer clinical outcomes in acute ischemic stroke. Given the ease of SUA measurement, its integration into stroke assessment protocols could enhance prognostic accuracy. However, further multicentric studies with larger sample sizes and neuroimaging data are needed to establish its utility as a standalone biomarker. KEYWORDS Stroke, serum uric acid (SUA), National Institute of Health Stroke Scale (NIHSS)